EPR spectroscopy and its use in planta—a promising technique to disentangle the origin of specific ROS - Steffen-Heins, Anja; Steffens, Bianka (Frontiers in Environmental Science, 2015)
While it is widely accepted that reactive oxygen species (ROS) are common players in developmental processes and a large number of adaptations to abiotic and biotic stresses in plants, we still do not know a lot about ROS level control at cellular or organelle level. One major problem that makes ROS hard to quantify and even to identify is their short lifetime. A promising technique that helps to understand ROS level control in planta is the electron paramagnetic resonance (EPR) spectroscopy. Application of the spin trapping method and the spin probe technique by this advanced method enables the quantification and identification of specific ROS in different plant tissues, cells or organelles or under different conditions. This mini review summarizes the knowledge using EPR spectroscopy as a method for ROS detection in plants under different stress conditions or during development. This technique allows disentangling the origin of specific ROS and transient alteration in ROS levels that occur by changes in ROS production and scavenging.